First whole-genome shotgun sequence of a promising cellulase secretor, Trichoderma koningiopsis strain POS7 - Castrillo, María Lorena (2017)
Trichoderma koningiopsis strain POS7 produces significantly large amounts of cellulase enzymes in solid-state fermentation. The Illumina-based sequence analysis reveals an approximate genome size of 36.6 Mbp, with a G+C content of 48.82% for T. koningiopsis POS7. Based on ab initio prediction, 12,661 coding genes were annotated.